Odpowiedzi

Najlepsza Odpowiedź!
2009-11-19T21:22:12+01:00
A). 7(x² - 3x - 2) -3 (x² - 6x + 1 ) ? dla x = - 0.2
7[(-0.2)²-3(-0.2) - 2] - 3[(-0.2)²-6(-0.2)+1] =
7(0.04+0.6-2) -3(0.04+1.2+1) = 7(-1,36) - 3×2.24 = -9.52 -6,72= -16.24

b). x(3xy - y) - y (x² - xy + x) ? dla x = -1 , y = 1/5 .
-1[3(-1)⅕ - ⅕] - ⅕ [(-1)² - (-1)⅕ + (-1)]=
-1[(-0.6)-0.2 ]- 0.2(1+0.2-1)= -1(-0.8)- 0.2×0.2 = 0.8 - 0.04 = 0.76
2009-11-19T22:36:34+01:00
A). 7(x² - 3x - 2) -3 (x² - 6x + 1 ) =
=7x²-28x-14-3x²+18x-3=
=5x²-10x-17
i podstawiamy
5*(-0,2)²-10*(-0,2)-17=
=5*0,04-2-17=
0,2-2-17=(-18,8)
b). x(3xy - y) - y (x² - xy + x)=
=4xy-xy-x²y+2yx-xy=
=2xy-x²y+2yx
i podstawiamy
2*(-1)*¹/₅-(-1)²*¹/₅+2*¹/₅*(-1)=
=2*(-1)-¹/₅-1*¹/₅+2*¹/₅*(-1)=
=(-²/₅)-¹/₅+(-²/₅)=¹/₅
2009-11-20T00:37:52+01:00
A) 7(x²-3x2)-3(x²-6x+1) dla x=-0,2

7x²-21x-14-3x²+18x-3 = 4x²-3x-17 = 4(-0,2)²-3(-0,2)-17 = 4*0,04+0,6-17 = 0,16+0,6-17 = -16,24

b) x(3xy-y)-y(x²-xy+x) dla x =-1 , y=1/5

x(3xy-y)-y(x²-xy+x) = 3x²y-xy-x²y+xy²-xy = 2x²y-2xy+xy² = 2(-1)²0,2-2(-1)0,2+(-1)0,2² = 2*0,2+2*0,2-0,04 = 0,8-0,04 = 0,76